2015
DOI: 10.1111/jgh.13068
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic silencing of NDRG2 promotes colorectal cancer proliferation and invasion

Abstract: Epigenetic silencing of NDRG2 induces proliferation and invasion of CRC and may be associated with proximal CRC and advanced T stage. NDRG2 methylation might serve as novel biomarker of CRC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 22 publications
1
25
0
Order By: Relevance
“…Hong and collaborators found that epigenetic silencing of NDRG2 induced proliferation and invasion of primary colorectal cancer cells, and that this could be associated with advanced stages of the disease (49). Similarly, Lee and collaborators found that in patients with gallbladder carcinoma loss of NDRG2 expression was an independent predictor of decreased patient survival and was significantly associated with a more advanced tumor stage (32).…”
Section: Discussionmentioning
confidence: 99%
“…Hong and collaborators found that epigenetic silencing of NDRG2 induced proliferation and invasion of primary colorectal cancer cells, and that this could be associated with advanced stages of the disease (49). Similarly, Lee and collaborators found that in patients with gallbladder carcinoma loss of NDRG2 expression was an independent predictor of decreased patient survival and was significantly associated with a more advanced tumor stage (32).…”
Section: Discussionmentioning
confidence: 99%
“…SW480 and SW620) show minimal NDRG1 CpG island methylation [53] and a number of GI-cancer cell lines and colon cancer tissues show variable NDRG2 promoter hypermethylation at several CpG sites, with levels ranging between 27 to 100% [45,[57][58][59][60]. Promoter hypermethylation of NDRG2 corresponds well with reduced NDRG2 expression in CRC [45,[57][58][59][60]. In fact, 84-100% of the hypermethylated tissues lack NDRG2 mRNA expression and immunoreactivity [57][58][59].…”
Section: Epigenetic Changesmentioning
confidence: 99%
“…Promoter hypermethylation of NDRG2 corresponds well with reduced NDRG2 expression in CRC [45,[57][58][59][60]. In fact, 84-100% of the hypermethylated tissues lack NDRG2 mRNA expression and immunoreactivity [57][58][59]. The differential methylation pattern could be explained by the presence of several transcription start sites (TSS) with distinct promoters having CpG islands, primarily located in exon 1 and 2 of the NDRG2 gene [50], and the use of different primer sequences to analyze the methylation status of the NDRG2 promoter [45,50,58,59,61].…”
Section: Epigenetic Changesmentioning
confidence: 99%
“…Also, NDRG2 upregulation was associated with Alzheimer's disease or cerebral ischemia [21, 22]. Several studies have shown NDRG2 promoter CpG island methylation and down-regulation in liver [13], gastric [10], colorectal cancers (CRC) [23, 24], glioblastomas [8, 9] and anaplastic meningioma [25]. However, NDRG2 promoter methylation and mRNA expression levels in PAs has not been investigated.…”
Section: Introductionmentioning
confidence: 99%